University of Washington campus looking west from atop the old Forestry Building toward Portage Bay and the Latona Bridge, Seattle, approximately 1916 - Webster and Stevens
Shows buildings constructed for the 1909 Alaska Yukon Pacific Exposition. Old Washington State Building, later used as the library to the right, and the Oregon State Building (demolished in 1917) to the left. Drumheller fountain is to the far left. The view is taken from the Forestry Building that was used as a museum until 1927 when the museum was moved and the building was destroyed in 1930. Caption on image: 47154. W & S. PH Coll 195.11